Resonance applications in physical science - Woolfson, Michael M. Michael Mark (Imperial College Press, 2015)
This book explores a large number of resonance effects that occur both in everyday life and in scientific contexts. It is a topic that provides a cross-link between many branches of science and shows how a single scientific principle can manifest itself in many, apparently disparate, ways